2016
DOI: 10.5688/ajpe80230
|View full text |Cite
|
Sign up to set email alerts
|

Student Evaluation of Online Pharmaceutical Compounding Videos

Abstract: Objective. To describe pharmacy students' views on the effectiveness of an expansion of the compounding laboratory website at the UNC Eshelman School of Pharmacy. Methods. Originally, there were 39 videos and three animations available. In 2011, an additional 59 videos and two animations were added. Concurrently, all of the interactive questions were updated to fully integrate with the expanded video library. Students were surveyed about the expanded video library regarding accessibility, functionality, and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…From these, z-scores were calculated to be applied in the statistical testing of hypotheses. Other research works, including those focused on the field of education, often utilize other statistical methods as well [78][79][80][81][82], but their application is based on working with the numeric data type.…”
Section: Methodsmentioning
confidence: 99%
“…From these, z-scores were calculated to be applied in the statistical testing of hypotheses. Other research works, including those focused on the field of education, often utilize other statistical methods as well [78][79][80][81][82], but their application is based on working with the numeric data type.…”
Section: Methodsmentioning
confidence: 99%
“…Learning was also assessed subjectively, through pre-, mid-and post-intervention surveys in twenty-six (46.4%) studies [11,12,[14][15][16][17][18][19]23,25,29,30,35,37,[41][42][43]45,46,50,52,56,57,59,62,64] and all but two [19,42] of these studies reported that the e-learning intervention was effective. Taglieri et al, [19] investigated the effect of completion of online virtual patient cases on student performance and confidence in mock clinic visits.…”
Section: Interventionmentioning
confidence: 99%
“…Of the fifty-six studies that were reviewed, all were limited by methodological flaws. Thirty (53.6%) studies [11,12,[14][15][16][17]19,20,22,[27][28][29][30][31][32][33][35][36][37]43,46,47,49,[52][53][54]56,58,63,64] did not establish the baseline knowledge, confidence or skills of participants and this is significant in two regards: It does not allow accurate comparison between groups, as differences in baseline knowledge may be responsible for differences in final knowledge; and it does not allow the impact of the intervention in increasing students' performance to be quantified. Three (5.4%) [25,55,57] of the nine studies that reviewed blended learning methods, failed to assess the effectiveness of the e-learning intervention independently of the face-to-face teaching.…”
Section: Limitations Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report by Park and Shrewsbury 2 , students were asked their opinion about an expansion of the materials on the pharmlabs website (pharmlabs.unc.edu) 3 , one of the primary reference sources used in their compounding lab course. As part of that survey given at the completion of the course, they were asked one question about their confidence to compound acceptable preparations.…”
Section: Introductionmentioning
confidence: 99%